Engineering Information Security : The Application of Systems Engineering Concepts to Achieve Information Assurance - Jacobs, Stuart (New Jersey : John Wiley, 2011)
Information security is the act of protecting information from unauthorized access, use, disclosure, disruption, modification, or destruction. This book discusses why information security is needed and how security problems can have widespread impacts. It covers the complete security lifecycle of products and services, starting with requirements and policy development and progressing through development, deployment, and operations, and concluding with decommissioning. Professionals in the sciences, engineering, and communications fields will turn to this resource to understand the many legal, technical, competitive, criminal and consumer forces and influences that are rapidly changing our information dependent society.
Includes bibliographical references; Index 663-700p.
Keywords: Computer Science; Information security; Engineering